COGNITIVE MAPPING OF FORMULAIC LANGUAGE IN UZBEK, ENGLISH, AND RUSSIAN AS A CONCEPTUAL CORPUS STUDY (KONFERENSIYA, 2025)
This research investigates the cognitive representation and conceptual organisation offormulaic expressions in English, Russian, and Uzbek through a synthesis of usagebased linguistics, cognitive mapping, and corpus analysis. This study employsCOCA, the British National Corpus, and the Russian National Corpus, integratingconcepts from Construction Grammar, conceptual metaphor theory, and framesemantics to examine the functioning of linguistic units as symbolic form-meaningpairings shaped by frequency, entrenchment, and chunking. The study demonstratesthat formulaic expressions encapsulate both universal cognitive mechanisms,including metaphorization, personification, and prototype-based categorisation, aswell as culturally specific conceptualisations rooted in the worldview of eachcommunity. English terms emphasise human agency and practical problem-solving;Russian expressions highlight perseverance, fatalism, and philosophical reflection;while Uzbek expressions illustrate collectivist principles, agricultural symbolism, andspiritual notions of blessing and reverence. The research illustrates that by correlatinglinguistic patterns with conceptual domains such as time, effort, fate, socialconnections, and emotional experience, formulaic language serves as a cognitive toolfor structuring cognition and as a cultural artefact that embodies collective socialknowledge. The findings advance cross-linguistic cognitive research bydemonstrating how corpus-derived data and conceptual mapping techniques canreveal the deep cognitive and cultural foundations of formulaic expressions acrossmultiple languages